Searches for superparticles of CMSSM model at the LHC - Obikhod, T.V. (Вопросы атомной науки и техники, 2015)
Using the discovery of a SM-like Higgs boson by ATLAS and CMS Collaborations and the observation by CMS and LHCb of BR(Bs → μ⁺μ⁻) decay as well as 8 TeV ATLAS 20 fb⁻¹ jets + ET data set we received an indirect constraint on SUSY model parameters. Considering the constrained versions of the minimal supersymmetric extension of the Standard Model (CMSSM) we used SOFTSUSY and PROSPINO computer programs for calculations of masses and production cross sections of the superparticles, that could be discovered at the LHC. За допомогою даних відкритого ATLAS і CMS колабораціями CM-подібного бозону Хігса, вимірів CMS і LHCb колабораціями BR(Bs → μ⁺μ⁻), а також набору даних 8 TeV ATLAS 20 fb⁻¹ jets + ET, отримано непряме обмеження на параметри SUSY моделі. Розглядаючи обмежену версію Мінімальної суперсиметричної стандартної моделі (CMSSM), ми використовували комп'ютерні програми SOFTSUSY і PROSPINO для розрахунку мас і поперечних перерізів утворення суперчасток, які можуть бути відкриті на LHC. Используя данные открытого ATLAS и CMS коллаборациями CM-подобного бозона Хиггса, измерения CMS и LHCb коллаборациями BR(Bs → μ⁺μ⁻), а также набор данных 8 TeV ATLAS 20 fb⁻¹ jets + ET, получено непрямое ограничение на параметры SUSY модели. Рассматривая ограниченную версию Минимальной суперсимметричной стандартной модели (CMSSM), мы использовали компьютерные программы SOFTSUSY и PROSPINO для расчета масс и поперечных сечений образования суперчастиц, которые могут быть открытыми на LHC.